A Case Study of Rural Marketing Strategies of MNCs in India and Indonesia - Alka Maurya (Journal of International Conference Proceedings (JICP), 2018)
Multinational Companies in a bid to increase their revenue and profit are now eyeing the emerging markets. Further, considering the saturation in the urban market they are now eyeing the rural markets in these countries. Lowering price by reducing the volume, customization, mass production are the strategies of the past, these companies have now come up with innovative strategies wherein they involve the rural population so that they help them in reaching to the customers in the remotest part of the country. This case study is an attempt to study the strategies used by the companies to reach the rural population in India and Indonesia. Keywords: MNC, Emerging markets, India, Indonesia